Empowering Mothers through Education and Light Hypnosis for Members of the PKK and Dharma Wanita in Karangbinangun Subdistrict, Lamongan Regency to Foster Happiness - Chayatun Machsunah, Yayuk; Pratama, Dita (Academia Publication, 2025)
This community service article aims to enhance the understanding and skills of PKK and Dharma Wanita members in developing personal happiness while remaining empowered, productive, and socially engaged. The activity was conducted on October 14, 2025, at the Karangbinangun Subdistrict Hall, Lamongan Regency, and involved 70 participants. The methods included interactive lectures, participatory discussions, and affirmative relaxation sessions to support emotional management and self-confidence. Evaluation was carried out using a simple pre- and post-test measuring happiness levels and work motivation. The results indicated an increase in average happiness scores from 68 to 85 and work motivation from 70 to 88. Participant feedback also showed greater optimism, improved readiness to face family challenges, and increased motivation to participate in social and creative economic activities. Overall, the program had a positive impact on individual emotional well-being and strengthened the role of women as agents of change in the community.